Efficiency in improving health and education outcomes: Provincial and state-level estimates for Argentina and Mexico - Jayasuriya, Ruwan; Wodon, Quentin (Estudios Económicos de El Colegio de México, 2007)
Provincial and state-level analyses are conducted using panel data sets for Argentina and Mexico to assess the efficiency of provinces and states in improving health and education outcomes. Stochastic frontier estimation methods are used to determine optimal outcomes that could be reached with current resources, and to measure efficiency in reaching these benchmarks. The method is potentially useful since it enables the analyst to assess whether lagging regions have a lower performance due to a lack of resources, or a lack of efficiency in using their available resources.